Evaluation and nutritional management of fodder crops in summer rice fallows - SaliniRani V G (Department of Agronomy, College of Agriculture, 2001)
A field experiment was conducted at the Cropping Systems Research Centre, Karamana, Thiruvananthapuram during February, 2000 • - May, 2000 to evaluate the production potential and quality of different fodder crops in summer rice fallows and to study the changes in physio- chemical properties of soil due to fodder cropping and to work out the economics of fodder production. The treatment consisted of combined application of two levels of vermicompost (2.5 t ha' and 5 t ha") and two levels of chemical fertilizers (50 per cent and 100 per cent POP recommendation) on two cereal fodders (bajra and sorghum) and two leguminous fodders (Sesbania rostrata and cowpea). The experiment was laid out in split plot design with four replications. Plant height, leaf area index and leaf: stem ratio differed significantly with the application of different combinations of vermicompost and chemical fertilizers. All these parameters were found to be increasing with increasing levels of vermicompost and chemical